Current knowledge of thrombocytopenia in sepsis and COVID-19 - Cheng, Junjie; Zeng, Hanhai; Chen, Huaijun; Fan, Linfeng; Xu, Chaoran; Huang, Huaping; Tang, Tianchi; Li, Min (Frontiers in Immunology, 2023)
Thrombocytopenia, characterized by a decrease in platelet count, is commonly observed in sepsis and COVID-19. In sepsis, thrombocytopenia can result from various mechanisms, including impaired platelet production in the bone marrow, accelerated platelet destruction due to increased inflammation, sequestration of platelets in the spleen, immune-mediated platelet destruction, or dysregulated host responses. Similarly, thrombocytopenia has been reported in COVID-19 patients, but the immune-related mechanisms underlying this association remain unclear. Notably, interventions targeting thrombocytopenia have shown potential for improving outcomes in both sepsis and COVID-19 patients. Understanding these mechanisms is crucial for developing effective treatments.